Analisis Deskriptif Kepuasan Kerja Pegawai Sekretariat DPRD Kabupaten Lombok Timur - Busyairi, Ahmad; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2024)
An important factor in encouraging employees to function their thoughts and feelings at work is the satisfaction factor at work or what is called by job satisfaction. However, job satisfaction is often ignored in its urgency in encouraging employees to provide their best performance for the organization. This study was conducted to determine the level of job satisfaction of employees of the East Lombok Regency DPRD secretariat using five dimensions, namely the job itself, compensation, superiors/leaders, coworkers and promotions. The method was used descriptive quantitative. The population amounted to 63 employees with the census technique in sampling the research. The results of this study indicate that the level of job satisfaction in the job dimension itself was in the satisfied category with a scale range of 255, the compensation dimension was in the moderately satisfied category with a scale range of 215, the leadership dimension was in the satisfied category with a scale range of 266, the coworker dimension was in the satisfied category with a scale range of 267, and the promotion dimension was in the 212 scale range with a moderately satisfied category.